Characterization of Iodine-Related Molecular Processes in the Marine Microalga Tisochrysis lutea (Haptophyta) - Hernández Javier, Laura; Benzekri, Hicham; Gut, Marta; Claros, M. Gonzalo; van Bergeijk, Stefanie; Cañavate, José Pedro; Manchado, Manuel (Frontiers in Marine Science, 2018)
Iodine metabolism is essential for the antioxidant defense of marine algae and in the biogeochemical cycle of iodine. Moreover, some microalgae can synthetize thyroid hormone-like compounds that are essential to sustain food webs. However, knowledge regarding iodine-related molecular processes in microalgae is still scarce. In this study, a de novo transcriptome of Tisochrysis lutea cultured under high iodide concentrations (5 mM) was assembled using both long and short reads. A database termed IsochrysisDB was established to host all genomic information. Gene expression analyses during microalgal growth showed that most of the antioxidant- (aryl, ccp, perox, sod1, sod2, sod3, apx3, ahp1) and iodide-specific deiodinase (dio) genes increased their mRNA abundance progressively until the stationary phase to cope with oxidative stress. Moreover, the increase of dio mRNA abundance in aging cultures indicated that this enzyme was also involved in senescence. Cell treatments with iodide modified the expression of perox whereas treatments with iodate changed the transcript levels of gpx1 and ccp. To test the dependence of perox on iodide, microalgae cells were treated with hydrogen peroxide (H2O2) either in presence or absence of iodide observing that several genes related to reactive oxygen species deactivation (perox, gpx1, apx2, apx3, ahp1, ahp2, sod1, sod3 and aryl) were transcriptionally activated although with some temporal differences. However, only the expression of perox was dependent on iodide levels indicating this enzyme, acquired by horizontal gene transfer, could act as a haloperoxidase. All these data indicate that T. lutea activates coordinately the expression of antioxidant genes to cope with oxidative stress. The identification of a phase-regulated deiodinase and a novel haloperoxidase provide new clues about the origin and evolution of thyroid signaling and the antioxidant role of iodine in the marine environment.